Environmental assessment of additive manufacturing in the automotive industry. (20th July 2019) - Böckin, Daniel; Tillman, Anne-Marie
Abstract: 3D-printing, also known as Additive Manufacturing (AM), is an emerging technology with suggested potential to decrease environmental impacts in the manufacturing industry. Potential benefits from implementing the technology include reduced product weight, transportation and material losses, as well as improved functionality and possibility for printing of spare parts. Possible drawbacks are increased energy use in production and the slow printing process. As the technology is expected to grow significantly, it is important to assess potential environmental effects of implementation. In this study a Life Cycle Assessment (LCA) is used in the case of Powder Bed Fusion (PBF) of the metal parts of an engine in a light distribution truck. Conventional manufacturing is compared to scenarios with 3D-printing, one representing the present state of development of 3D-printing technology and one representing a possible future state. The results show that, in the future case, PBF potentially improves life cycle environmental performance by redesigning components for weight reduction. However, a clean electricity source was required as well as technological development allowing for printing of large components, with low-impact raw materials. When instead assessing AM in its present state of development, results showed only moderate or negligible environmental improvements. To achieve the future potential environmental benefits from AM it is important to use clean electricity and to develop the technology to be able to use low-impact feedstock materials such as low-alloy steel (avoiding materials based on e.g. nickel). Industries implementing AM should seek to exploit the benefits of the technology, such as weight reduction and functionality improvements as well as the potential offered for printing spare parts for remanufacturing and repairing. Highlights: Life Cycle Assessment comparing conventional and Additive Manufacturing of engine. Assessment includes potential technological development of Powder Bed Fusion. Potential for metal Additive Manufacturing to reduce vehicle life cycle impacts. Key factors are electricity mix, choice of material and redesign for lower weight.